Additional behavioural support as an adjunct to pharmacotherapy for smoking cessation - Hartmann-Boyce, J; Hong, B; Livingstone-Banks, J; Wheat, H; Fanshawe, TR (Cochrane Collaboration, 2019)
Background Pharmacotherapies for smoking cessation increase the likelihood of achieving abstinence in a quit attempt. It is plausible that providing support, or, if support is offered, offering more intensive support or support including particular components may increase abstinence further.